2021
DOI: 10.1111/ced.14770
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological surgery: an update on suture materials and techniques. Part 1

Abstract: Significant variation exists in the surgical suture materials and techniques used for dermatological surgery. Many wound-closure techniques are now practised, including use of sutures, staples and topical adhesives. The focus of our review article is to summarize the latest evidence relating to suture materials and wound-closure techniques, considering the following areas: scar/cosmesis, pain, patient satisfaction, cost, infection and wound complications. We searched the databases Medline, PubMed and Embase us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…26 Although RSC has been shown to have superior wound perfusion and cosmesis across multiple surgical subspecialties, its effect on postoperative wound complications in orthopaedic surgery is scarce and conflicting. [13][14][15][16][17][18][19][20][21] A meta-analysis of 6 studies by Smith et al 4 found that the risk of postoperative wound complications was 3.8 times greater for patients who received staples compared with those who received sutures. A subsequent systematic review and meta-analysis of 12 studies by Krishnan et al 5 found no differences in the rate of wound complications between these groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Although RSC has been shown to have superior wound perfusion and cosmesis across multiple surgical subspecialties, its effect on postoperative wound complications in orthopaedic surgery is scarce and conflicting. [13][14][15][16][17][18][19][20][21] A meta-analysis of 6 studies by Smith et al 4 found that the risk of postoperative wound complications was 3.8 times greater for patients who received staples compared with those who received sutures. A subsequent systematic review and meta-analysis of 12 studies by Krishnan et al 5 found no differences in the rate of wound complications between these groups.…”
Section: Discussionmentioning
confidence: 99%
“…4–14 More recently, studies in multiple surgical subspecialities have demonstrated that running subcuticular closures (RSC) result in improved wound perfusion and cosmesis when compared with staples or cutaneous mattress suture closures (CMC). 15–21 However, the use of RSC in orthopaedic trauma remains poorly studied and rarely used because of concern for increased risk of wound complications. 1,9,11,13,22…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once infection occurs, the whole stitch needs to be removed, hindering the healing process. 25 , 26 , 27 Pus could be drained by selectively removing a single stitch in interrupted sutures.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it shows low efficiency; it is difficult to control the absorption period and ensure that the sutures begin to degrade after wound healing. [15][16][17] (2) Medical adhesives, widely used in clinical practice, are prone to promoting rash or skin abnormalities after use, and some of them exhibit defects, such as a brittle adhesive layer, formaldehyde production during decomposition and poor air permeability. 18,19 (3) Although wound dressings can temporarily protect the wound, prevent contamination, promote healing and provide a suitable environment for the process of wound healing and treatment, they have the defects of a short efficacy duration and uneven sustained release.…”
Section: Introductionmentioning
confidence: 99%